Effects of 3R, 16S-2-hydroxyethyl apovincaminate (HEAPO), donepezil and galantamine on learning and memory retention in naïve Wistar rats - Dimitrova Darinka; Getova Damianka; Saracheva Kremena (Acta Pharmaceutica)
The effects of 3R,16S-2-hydroxyethyl apovincaminate (HEAPO, RGH-10885) compared with those of two cholinesterase inhibitors, donepezil and galantamine, were examined in naïve Wistar rats using standard active and passive avoidance tests. The active avoidance test (shuttle box) and two passive avoidance tests (step-through and step-down) were performed according to the experimental design. There were 10 groups of rats (n = 8) and the substances studied were applied orally before each testing session. In the active avoidance test, the number of conditioned stimuli (avoidances), unconditioned stimuli (escapes) and intertrial crossings were observed. In step-down and step-through passive avoidance tests, the latencies of reactions were observed. All the studied compounds showed positive effects in the learning and memory tests, compared to the controls. It was concluded that HEAPO, donepezil and galantamine had a memory-enhancing effect in active and passive avoidance tests.